Caribbean vocational qualification (CVQ) : requirements and guidelines for school administrators and principals (CXC BridgetownBB)
Provides requirements for the delivery of the Caribbean Vocational Qualification in schools; quality control procedures; administration of CVQ; readiness checklist.
Keywords: VOCATIONAL EDUCATION